Penerapan Pelaporan Keuangan Pondok Pesantren Miftahul Huda Smk It Al-Kasyaf Sukabumi Berdasarkan Pedoman Akuntansi Pesantren - Muzdhalifa, Tazha Yan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
Islamic Boarding School is a non-profit entity because Islamic Boarding Schools have an important role in the development of progress in Indonesia, this can be proven by the birth of warriors, leading Islamic scientists and others. And also what we can know that the financial value of Islamic boarding schools is quite large. Therefore, the issuance of Islamic Boarding School Accounting Guidelines issued by Bank Indonesia in order to assist in the preparation of financial reports at Islamic Boarding Schools. The purpose of this study is to find out how the presentation of financial statements by the Islamic Boarding School at Miftahul Huda SMK IT Al-Kasyaf Sukabumi is in accordance with the existing Islamic Boarding School Accounting Guidelines. The research method used in this study is a qualitative method, with observation, collecting data, then interviews and also documentation at the Islamic Boarding School at Miftahul Huda SMK IT Al-Kasyaf Sukabumi. The results of the research at the Islamic Boarding School at Miftahul Huda SMK IT Al-Kasyaf Sukabumi show that this Islamic Boarding School is still recording simple financial reports, namely only recording cash in and cash out, and also not implementing financial reports based on the Accounting Guidelines for Islamic Boarding Schools. Then the researcher provides recommendations for financial statements in accordance with Islamic Boarding School Accounting Guidelines. Therefore, the researchers suggest that Islamic Boarding Schools in Indonesia can implement the preparation of their financial statements with existing standards, because advanced Islamic Boarding Schools are able to manage their financial records and reporting properly and of good quality. Keywords: Islamic boarding school, financial reports, islamic boarding school accounting guidelines